2011
DOI: 10.1016/j.jesp.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Thou shalt not discriminate: How emphasizing moral ideals rather than obligations increases Whites' support for social equality

Abstract: An important step toward reducing group-based disparities in society is creating support for equality among advantaged group members (e.g., Whites, men). The current research examined how presenting social equality between ethnic groups in terms of moral ideals (i.e., equal treatment) vs. moral obligations (i.e., non-discrimination) affected the attitudes of Whites (students in Study 1, N = 45 and 2, N = 44 and employees in Study 3a, N = 67 and Study 3b, N = 62) toward various social equality issues. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 54 publications
4
63
0
1
Order By: Relevance
“…This proposition receives support from other recent research: Does et al (2011) showed that moral ideals (ought) are better suited for motivating the intended change in behaviour than moral obligations (must). Other research suggests that people can easily construe issues in either moral or non-moral terms.…”
Section: Potential Solution 1: Non-moral Framing Of Persuasive Messagessupporting
confidence: 63%
“…This proposition receives support from other recent research: Does et al (2011) showed that moral ideals (ought) are better suited for motivating the intended change in behaviour than moral obligations (must). Other research suggests that people can easily construe issues in either moral or non-moral terms.…”
Section: Potential Solution 1: Non-moral Framing Of Persuasive Messagessupporting
confidence: 63%
“…An interesting direction for future research would be to examine the potential utility of moral opportunity for motivating participants to actively improve group conduct. The current findings suggest there may be particular value in reparation measures that focus on opportunities to improve moral practices in the future rather than ways of redressing the moral transgressions of the past (see also Does et al, 2011). Thus, rather than asking individual group members whether they think they should take responsibility for the consequences of past moral transgressions, it might be more appropriate to capture the impact of providing people with moral opportunity by assessing their willingness to be involved or invest effort in the development or adoption of novel measures to improve moral behavior in the future (see also Zimmermann, Abrams, Doosje, & Manstead, 2011).…”
Section: Discussionmentioning
confidence: 87%
“…The way in which social equality is connected to moral goals does matter, though. Whereas moral ideals can challenge people to achieve these goals, setting equality as a moral obligation tends to raise threat and resistance (Does et al., 2011, Does et al., 2012).…”
Section: Intergroup Relationsmentioning
confidence: 99%
“…When the moral ideal of equal opportunities (in this case on the labor market) for members of different ethnic groups is made explicit, majority group members can be activated to improve equality. They then indicate personal commitment to achieving the goal of equality and are inclined to support affirmative action and cultural diversity (Does, Derks, & Ellemers, 2011). The way in which social equality is connected to moral goals does matter, though.…”
Section: Intergroup Relationsmentioning
confidence: 99%